Toward diagnostics of water-lubricated bearings of naval vessels by vibration analysis. (July 2023) - Matania, Omri; Heletz, Shani; Klein, Renata; Groper, Morel; Bortman, Jacob
Sliding bearings are mechanical components used for rotor support of high-load mechanical systems. It is assumed that a change in the lubrication regime at a known operational point is a result of an anomaly in the bearing operation such as an increased load, lack of lubricant, and damage to the bearing surface or wear. Detection of this phenomenon will enable diagnostics of the bearing. In this study, we present a novel technique for estimating the transition point between synchronous and asynchronous interactions of the shaft and bearing which is related to the transition between lubrication regimes of a water-lubricated bearing of a marine vessel by vibration analysis. The new technique is demonstrated on an experimental system that reproduces the operation of a water-lubricated bearing. The results demonstrate the ability of using vibration analysis to identify changes in the operating condition of a water-lubricated bearing.